Polyethylene Glycol Coatings on Plastic Substrates for Chemically Defined Stem Cell Culture. Issue 10 (20th May 2015) - Schmitt, Samantha K.; Xie, Angela W.; Ghassemi, Raha M.; Trebatoski, David J.; Murphy, William L.; Gopalan, Padma
<x xml:space="preserve">Abstract</x> Human mesenchymal stem cells (hMSCs) are a widely available and clinically relevant cell type with a host of applications in regenerative medicine. Current clinical expansion methods can lead to selective changes in hMSC phenotype potentially resulting from relatively undefined cell culture surfaces. Chemically defined synthetic surfaces can aid in understanding the influence of cell–material interactions on stem cell behavior. Here, a thin copolymer coating for hMSC culture on plastic substrates is developed. The random copolymer is synthesized by living free radical polymerization and characterized in solution before application to the substrate, ensuring a homogeneous coating and limiting the sample‐to‐sample variations. The ability to coat multiple substrate types and cover large surface areas is reported. Arg–Gly–Asp‐containing peptides are incorporated into the coating under aqueous conditions via their lysine or cysteine side chains, resulting in amide and thioester linkages, respectively. Stability studies show amide linkages to be stable and thioester linkages to be labile under standard serum‐containing culture conditions. In addition, chemically defined passaging of hMSCs using only ethylenediaminetetraacetic acid on polystyrene dishes is shown. After passage, the hMSCs can be seeded back onto the same plate, indicating potential reusability of the coating.